The Specialization and Semantics Interpretation of Teacher Talk of Civil Engineering English MOOC In China: The Legitimation Code Theory Perspective - Dai, Fengju; Chengyu, Liu (Universitas Pendidikan Mandalika, 2023)
With the economic development of China, the need for Civil Engineering talents with English language skills is continuously increasing. To meet this need, Civil Engineering English teaching plays a significant role. This paper takes the Civil Engineering English MOOC provided by a university located in eastern China, as an example, and takes two dimensions of the Legitimation Code Theory, specialization and semantics to investigate the following research questions: (RQ1) What are the textual semantic features, specialization and semantics characteristics of the selected Civil Engineering textbook? (RQ2) What â€œunpackingâ€ strategies does the teacher adopt in the teaching process and what are the textual semantic features, specialization, and semantics characteristics of teacher talk in the MOOC? (RQ3) From the perspective of specialization and semantics dimensions, are there any deficiencies in this MOOC? The purpose is to analyze the â€œunpackingâ€ strategies in teacher talk and the possible problems in the teaching process. The content analysis method is employed, and the data include two aspects: one is the textbook the MOOC adopted; the other is the teacher talk. Through the analysis, we draw the following conclusions: the teaching material shows the characteristics of high lexical difficulty and high semantic density; in the teaching process, the teacher, who works as an â€œintermediaryâ€, mainly adopts â€œunpackingâ€ strategies such as transforming knowledge code into knower code, improving learnersâ€™ knowledge code, and reducing semantic density. However, some defects such as the lack of knower code in teaching content, semantic wave fracture, and the weak comprehensibility of the input content make it difficult to achieve the teaching goal of mastering the elite code. Given these defects, this paper tentatively puts forward some suggestions based on the adopted theory.